Validated algorithms for identifying timing of second event of oropharyngeal squamous cell carcinoma using real‐world data - Khair, Shahreen; Dort, Joseph C.; Quan, May Lynn; Cheung, Winson Y.; Sauro, Khara M.; Nakoneshny, Steven C.; Popowich, Brittany Lynn; Liu, Ping; Wu, Guosong; Xu, Yuan (Head & neck, 2022)
Background Understanding occurrence and timing of second events (recurrence and second primary cancer) is essential for cancer specific survival analysis. However, this information is not readily available in administrative data. Methods Alberta Cancer Registry, physician claims, and other administrative data were used. Timing of second event was estimated based on our developed algorithm. For validation, the difference, in days between the algorithm estimated and the chart‐reviewed timing of second event. Further, the result of Cox‐regression modeling cancer‐free survival was compared to chart review data. Results Majority (74.3%) of the patients had a difference between the chart‐reviewed and algorithm‐estimated timing of second event falling within the 0–60 days window. Kaplan–Meier curves generated from the estimated data and chart review data were comparable with a 5‐year second‐event‐free survival rate of 75.4% versus 72.5%. Conclusion The algorithm provided an estimated timing of second event similar to that of the chart review.